Discharge Planning Method of Diatohc (Diabetes Transition of Hospital Care) for Readmission Prevention - Yeni Hartati; Fitrian Rayasari; Dewi Anggraini; Wati Jumaiyah; Uswatun Hasanah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes mellitus is a metabolic disorder characterized by increased blood sugar levels (hyperglycemia) caused by lack of insulin, inability of insulin to work or both. Lack of education or information from health workers can have an impact on patient compliance with treatment, which will result in repeated treatment. This innovation program aims to reduce the risk of readmission in Diabetes Mellitus patients by providing integrated education using the DiaTOHC method, patients who are screened using the DERRI application if the score is > 27%, patients are at risk of readmission, then they will be given education using the DiaTOHC method, which is integrated education. When patients are treated, they will be given education on the 5 pillars, after the patient goes home during the control, they will be reviewed whether there are any obstacles or obstacles in the treatment, then in weeks 2, 3 and 4 the patient will be contacted by telephone for re-education and evaluation of treatment. The results of the trial of this program from 17 samples were successful, all of which were readmissions, it was concluded that there was effectiveness in providing education using the DiaTOHC method in Diabetes Mellitus patients to reduce the risk of readmission. Data is collected by interview, observation and filling out questionnaires, after the data is collected, data analysis is carried out by inputting all data found in excel software and then assessing the percentage of patients who are readmitted.